Pengaruh Model Learning Cycle 5E Berbantuan Mind map Terhadap Pengetahuan Faktual Dan Konseptual Pada Pembelajaran IPA Siswa Kelas V Sekolah Dasar - Isna Fiky Nalansari; Endang Widi Winarni; Neza Agusdianita (JURIDIKDAS, 2020)
This study aims to determine the effect of the use of the Learning cycle 5E assisted by Mind map on the factual and conceptual knowledge of grade V elementary school students on the learning of science. This type of research is quantitative research. The research method used was quasi experimental with the type of matching the pretest-posttest control group design. The population in this study was elementary school XIX Bengkulu City. The sampling technique uses cluster random sampling. The sample in this study is the VA class SDN 69 Bengkulu City totaling 30 students as the experimental class and the VB class SDN 72 Bengkulu City totaling 25 students as the control class. The research instrument used in this study was in the form of mind map quality assessment sheets and factual and conceptual knowledge assessment test sheets in the form of multiple choice given at the pre-test and post-test. The data analysis technique in this research is quantitative analysis using descriptive statistics and inferential statistics, the t-test. The research data obtained tcount> ttable, namely factual knowledge 2.31> 2.01 and conceptual knowledge 3.30> 2.01. Thus it can be concluded that there is an influence of the use of the 5E Learning cycle model with a mind map to the factual and conceptual knowledge of students in the learning of science class V in elementary school.